Analisis Kesesuaian Masa Jabatan Pengurus RT dalam Peraturan Bupati Nomor 24 Tahun 2020 - Anita Anita; M. Syahrul Borman; Nur handayati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the suitability of the term of office of the Neighborhood Association (RT) administrators with the provisions contained in Regent Regulation Number 24 of 2020 concerning the Organization and Work Procedures of Neighborhood Associations. The term of office of RT administrators is an important aspect in running the government at the village/sub-district level which affects the effectiveness of community services and the sustainability of development programs. Through a normative legal research approach, this study examines whether the provisions on the term of office of RT administrators stated in the regulation are in accordance with applicable legal principles, community needs, and practices in the field. The research methods used are document studies, interviews with RT administrators and related parties, and comparative analysis with similar policies in other areas. The results of the study indicate that there are several discrepancies between the provisions on the term of office stated in the Regent Regulation and the real conditions that occur in the field. Some RT administrators have difficulty in carrying out a term of office that is too short, while others feel that a term of office that is too long can hinder the regeneration of the administration. This study recommends that there be a revision to the Regent Regulation Number 24 of 2020, by considering the existing findings, and providing space for the community to participate more actively in the process of replacing RT administrators.